Nematic field transfer in a two-dimensional protein fibril assembly. Issue 6 (7th January 2016) - Jordens, Sophia; Schwenke, Konrad; Usov, Ivan; Del Gado, Emanuela; Mezzenga, Raffaele
Abstract : Experiments and simulations on bimodal solutions of amyloid fibrils at liquid interfaces reveal length-scale dependent orientation and 2D nematic field transfer. Abstract : We perform Atomic Force Microscopy and numerical simulations of a bimodal solution containing long, semiflexible β-lactoglobulin fibrils and short, flexible β-lactoglobulin linear aggregates at an air–water interface. Short aggregates orient perpendicular to fibrils at very short distances and preferentially parallel at intermediate distances. At even larger distances an isotropic distribution is observed. Parallel ordering coincides with aggregate stretching: by straightening, small aggregates are able to approach the fibrils within a distance smaller than their radius of gyration. These findings contribute to the understanding of how anisotropic interactions are transferred in two-dimensional bimodal nematic fields of biopolymers at liquid interfaces.